Digestion - Parker, Steve, 1952- (Mankato, Minn. : Stargazer Books, 2005)
Presents a comprehensive look at the different parts of the digestive system and how they function.
Includes index.
Booklist.
L.A. Recommended Foreign Language.
Booklist, November 1997.
L.A. Recommended Foreign Language, February 1999.
5.8
Keywords: Digestion -- Juvenile literature; Digestive organs -- Juvenile literature; Digestive system; Digestion; Digestive organs